2019
DOI: 10.1111/aos.14284
|View full text |Cite
|
Sign up to set email alerts
|

Histological findings of levator muscle in unilateral congenital ptosis in different age groups

Abstract: Purpose: To evaluate the different degree of muscle atrophy in specimens of levator muscle of patients operated on for unilateral congenital ptosis, as related to the age of the patient. Methods: Histological analysis of the specimen of the levator muscle of 29 patients who underwent a unilateral levator muscle resection under the care of one surgeon was performed. The study population was divided into two different groups according to the timing of surgery: group 1 included 15 children operated on at 2 to 4 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Histopathological findings revealed fat infiltration, fibrosis, and decreased numbers of muscle fibers in the levator muscle in cases of congenital ptosis. 18 Moreover, there was an inverse correlation between the number of muscle fibers and the severity of ptosis, 19 which was consistent with a clinical phenomenon in which the levator muscle was gauzy and fragile in cases of severe congenital ptosis and was prone to collapse when dissociating it from the conjunctiva. The traditional levator resection technique involves separating the levator muscle completely, which will inevitably collapse the muscle.…”
Section: Discussionsupporting
confidence: 67%
“…Histopathological findings revealed fat infiltration, fibrosis, and decreased numbers of muscle fibers in the levator muscle in cases of congenital ptosis. 18 Moreover, there was an inverse correlation between the number of muscle fibers and the severity of ptosis, 19 which was consistent with a clinical phenomenon in which the levator muscle was gauzy and fragile in cases of severe congenital ptosis and was prone to collapse when dissociating it from the conjunctiva. The traditional levator resection technique involves separating the levator muscle completely, which will inevitably collapse the muscle.…”
Section: Discussionsupporting
confidence: 67%
“…In recent, the histological study of the CFS [ 1 ] and LM [ 21 ] has received much attention among ophthalmologists. In our study, the histological results showed that the CFS is a fibrous connective tissue membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital ptosis, especially moderate and severe ptosis, affects children’s visual function and aesthetics, and also interferes with their normal quality of life ( 11 , 12 ). Hypoplasia of the levator palpebral is the main pathogenesis in congenital cases, and may also be associated with dysgenesis or insufficiency of the central and peripheral nerves which innervate the levator palpebral ( 13 ). Early surgical correction to restore the visual function of children and improve the quality of life of children is the main treatment strategy at present, and the surgical method used has become a hot topic of clinical research.…”
Section: Discussionmentioning
confidence: 99%